Estudo da formação de microemulsões contendo óleo essencial de Citrus sinensis (L.) Osbeck : efeito dos co-tensoativos e avaliação da interação das microemulsões com modelo de estrato córneo - Resende, Quênnia Garcia Moreno (2013)
Microemulsions (MEs) are dispersed systems, thermodynamically stable, isotropic, transparent, and stabilized by an interfacial film of surfactant compounds. In this study were obtained MEs from differents co - surfactant (ethanol - ET, isopropanol-ISO and propylene glycol - PG), Citrus sinensis (L.) Osbeck essential oil (CSEO), Tween 80 ® and phosphate buffer (pH 5.0). The co - surfactants were selected because they are tolerated by the skin. Therefore, the aim of the study was to evaluate the influence of co - surfactants in the formation of MEs containing Tween 80, CSEO and evaluate the influence of nifedipine (NFD) in the structure of systems formed. The MEs were obtained by constructing diagrams of pseudo-ternary phase in order to evaluate the influence of co-surfactant in the formation of MEs. The structural characterization of these systems was obtained by Polarized Light Microscopy (MLP), test electrical conductivity and Small angle X-ray scattering (SAXS). In each diagram, two formulations were selected, which was the criterion sense phase, in the O / A and bicontinuous, in which the NFD is incorporated. The formulations were evaluated by the techniques mentioned, to observe the influence of NFD and characterized by pH, droplet size, polydispersity index (PDI), surface tension and rheology. Interaction studies with model stratum corneum (SC) were performed using the techniques of differential scanning calorimetry (DSC) and Fourier transform infrared spectroscopy (FTIR). In the diagrams showed the greatest formation region of the MEs to the ISO (above 40 % T / Cot) instead of the co- surfactants ET and PG. When assessing the electrical conductivity has been observed that increasing the aqueous fraction resulted in an increase in conductivity. The SAXS curves demonstrated that all systems are characteristic of micellar structures and as the water content was added, it was observed the formation of larger structures. Therefore, from the results obtained, the NFD has been incorporated in the formulations selected. The MEs presented as stable systems, isotropic, translucent droplet size between 16 and 34 nm, PDI below 0.5 and pH in the range of 5.64 to 6.7, compatible with the skin and pH stability of the NFD. In conductivity tests for each co - surfactant, the MEs were classified as bicontinuous and O / A. The MEs exhibited reduced surface tension and the formulations containing ISO submitted a surface tension value (24,764 mN / m) lower than the other co - surfactants (ET - 29.512 mN/m PG - 31.784 mN/m), confirmed by the evaluation of the droplet diameter and obtaining the phase diagram. The MEs exhibited Newtonian behavior, with consistency indices (k) higher in formulations with higher proportions of T / Cot, result corroborated the structures observed by SAXS. The DSC and FTIR techniques have demonstrated the use of the MEs as permeation promoters, provided from interactions with SC model. Therefore, the diagrams have elucidated the effect of co- surfactant in the formation of MEs and the same interference suffered no NFD, suggesting their use as permeation enhancers on the skin on application.